Role of Epstein-Barr Virus in Pathogenesis and Racial Distribution of IgA Nephropathy - Zachova, Katerina; Kosztyu, Petr; Zadrazil, Josef; Matousovic, Karel; Vondrak, Karel; Hubacek, Petr; Julian, Bruce A.; Moldoveanu, Zina; Novak, Zdenek; Kostovcikova, Klara; Raska, Milan; Mestecky, Jiri (Frontiers in Immunology, 2020)
IgA nephropathy (IgAN) is the dominant type of primary glomerulonephritis worldwide. However, IgAN rarely affects African Blacks and is uncommon in African Americans. Polymeric IgA1 with galactose-deficient hinge-region glycans is recognized as auto-antigen by glycan-specific antibodies, leading to formation of circulating immune complexes with nephritogenic consequences. Because human B cells infected in vitro with Epstein-Barr virus (EBV) secrete galactose-deficient IgA1, we examined peripheral blood B cells from adult IgAN patients, and relevant controls, for the presence of EBV and their phenotypic markers. We found that IgAN patients had more lymphoblasts/plasmablasts that were surface-positive for IgA, infected with EBV, and displayed increased expression of homing receptors for targeting the upper respiratory tract. Upon polyclonal stimulation, these cells produced more galactose-deficient IgA1 than did cells from healthy controls. Unexpectedly, in healthy African Americans, EBV was detected preferentially in surface IgM- and IgD-positive cells. Importantly, most African Blacks and African Americans acquire EBV within 2 years of birth. At that time, the IgA system is naturally deficient, manifested as low serum IgA levels and few IgA-producing cells. Consequently, EBV infects cells secreting immunoglobulins other than IgA. Our novel data implicate Epstein-Barr virus infected IgA+ cells as the source of galactose-deficient IgA1 and basis for expression of relevant homing receptors. Moreover, the temporal sequence of racial-specific differences in Epstein-Barr virus infection as related to the naturally delayed maturation of the IgA system explains the racial disparity in the prevalence of IgAN.